Socioeconomics of the Lionfish Derby Fishery - Trotta, Kristina Ann; Nardelli, Adam; Green, Stephanie; Adkins, Lad; Gentner, Brad; Kerstetter, David W. (NSUWorks, 2014)
Throughout the western North Atlantic Ocean, Caribbean Sea, and the Gulf of Mexico, invasive Indo-Pacific lionfish (Pterois volitans/miles) have established dense populations, greatly impacting their host environments. Lionfish tournaments have been an important tool for resource managers and other concerned stakeholders in suppressing local populations of lionfish. Tournaments can also bring economic benefits to the communities where they are held, despite this not being the primary purpose. Five derby events in Florida and the Bahamas were surveyed and 119 participants were interviewed on site, using a survey asking them to describe: (1) the lionfish derby experience; (2) non-derby related lionfish removal effort; (3) derby expenditures; and (4) personal characteristics. Response rates of event participants were between 35% and 82%. Respondents spent an average of approximately $820 per person, potentially creating a net economic benefit to the communities where they were held. Total expenditures reported ranged from $5,000 to over $60,000 per tournament, with events drawing a high number of out-of-town participants reporting the highest amounts spent. Participants surveyed were largely males who resided in Florida and had a reported income of over $100,000, with 29% indicating an annual income of more than $200,000. In addition, lionfish tournaments have the effect of educating the public about the lionfish invasion, including greater targeting and consumption of lionfish, showing that tournaments are effective at their conservation mission as well as contributing to the economy of their host community.